The Effect of Earnings Quality on Cost of Equity Capital (Survey Study on Companies Listed in Damascus Stock Exchange) - سوزان صالح; اياد حاتم; غيث جديد (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Companies aim to mitigate the imprecision risk that may be embedded in thier financial reporting by disclosing accurate earnings. which may reflect positively on future cash flow and consequently on the cost of companies’ equity. The aims of this research is to study the impact of Earnings Quality on Cost of Equity Capital, using a sample of 20 Companies listed on the Damascus Stock Exchange during the period from 2013-2020, based on cross-sectional data models to achieve this research. The cost of owned capital was measured using the Ohlson model (1995), and the approach to cash scale was used to measure the quality of profits. The results showed that there is no Statistically Significant Effect of the Quality of Earning on the Cost of Equity Capital, While the Results Showed that there is a positive Effect of the Earning Quality in the Cost of Capital after Adjusting the Size Variable, and a negative Effect after Adjusting the Financial Leverage Variable.